Influence of grinding procedures on the flexural strength of zirconia ceramics - İşerı,Ufuk (2010)
The surface of zirconia may be damaged during grinding, influencing the mechanical properties of the material. The purpose of this study was to compare the flexural strength of zirconia after different grinding procedures. Twenty bar-type zirconia specimens (21 x 5 x 2 mm) were divided into 4 groups and ground using a high-speed handpiece or a low-speed straight handpiece until the bars were reduced 1 mm using two different grinding times: continuous grinding and short-time grinding (n=5). Control specimens (n=5) were analyzed without grinding. The flexural strengths of the bars were determined by using 3-point bending test in a universal testing machine at a crosshead speed of 0.5 mm/min. The fracture load (N) was recorded, and the data were analyzed statistically by the Kruskal Wallis test at a significance level of 0.05. In the test groups, high-speed handpiece grinding for a short time had produced the highest mean flexural strength (878.5 ± 194.8 MPa), while micromotor continuous grinding produced the lowest mean flexural strength (733.8 ± 94.2 MPa). The control group was the strongest group (928.4 ± 186.5 MPa). However, there was no statistically significant differences among the groups (p>0.05). Within the limitations of the study, there was no difference in flexural strength of zirconia specimens ground with different procedures.